Strategi Internalisasi Nilai Pendidikan Islam Moderat Dalam Masyarakat Plural: Studi Kasus di Desa Balun Turi Lamongan - Faiqotul Abidah; Maftuh (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study examines the internalization of moderate Islamic educational values ​​towards a pluralistic society (a case study of Balun Turi Lamongan Village). Through this research, it can be explained about the internalization of moderate Islamic educational values ​​towards a pluralistic society (a case study of Balun Turi Lamongan village). This study aims to (1) To find out the Process of Internalizing the Values ​​of Moderate Islamic Education towards Pluralism Communities in Balun Village, Turi Lamongan District (2) To find out the values ​​of Moderate Islamic Education embedded in Pluralism Communities in Balun Village, Turi Lamongan District.This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Therefore, this research process is expected to produce descriptive data in the form of written or oral data from people or behavior that can be observed to provide an explanation of How the Process of Internalizing Moderate Islamic Education Values ​​Against Pluralism Communities in Balun Village, Turi Lamongan District and What Are the Values ​​of Moderate Islamic Education Embedded in a Pluralistic Society in Balun Village, Turi Lamongan District. The results of the study show (1) the values ​​of moderate Islamic education have been embedded in the minds of the Balun village community since the emergence of religions in Balun Village and the Balun Village community believes more in the role of a village head and religious figure in internalizing the values ​​of moderate Islamic education. in the Balun village community (2) the values ​​of Islamic education embedded in the Balun village community include Tasamuh values, Shura values, I'tidal values, Al-Musawah, islah values, tahaddur values, awlawiyah values, Wataniyah values ​​and Muwatanah